Geometric nonlinearities in field theory, condensed matter and analytical mechanics - Sławianowski, J.J. (Condensed Matter Physics, 2010)
There are two very important subjects in physics: Symmetry of dynamical models and nonlinearity. All really fundamental models are invariant under some particular symmetry groups. There is also no true physics, no our Universe and life at all, without nonlinearity. Particularly interesting are essential, non-perturbative nonlinearities which are not described by correction terms imposed on some well-defined linear background. Our idea in this paper is that there exists some mysterious, still incomprehensible link between essential, physically relevant nonlinearity and dynamical symmetry, first of all, of large symmetry groups. In some sense the problem is known even in soliton theory, where the essential nonlinearity is often accompanied by the infinite system of integrals of motion, thus, by infinite-dimensional symmetry groups. Here we discuss some more familiar problems from the realm of field theory, condensed matter physics, and analytical mechanics, where the link between essential nonlinearity and high symmetry is obvious, although not fully understandable. Зазначено, що у фізиці є два важливих предмети досліджень: симетрія динамічних моделей і нелінійність. Всі дійсно фундаментальні моделі є інваріантними щодо певних груп симетрії. Без нелінійності також нема ні справжньої фізики, ні нашого Всесвіту, ні життя взагалі. Особливо цікавими є незбурені нелінійності, які не описуються поправками, що накладаються на деякий добре визначений бекграунд. Ідея статті є така, що існує деякий таємничий, все ще незбагненний зв'язок між суттєвою фізично важливою нелінійністю та динамічною симетрією, насамперед, великих груп симетрії. В деякому сенсі ця проблема є відомою навіть в теорії солітонів, де суттєва нелінійність часто супроводжується нескінченною системою інтегралів руху - таким чином, нескінченновимірними групами симетрії. Розглянуто загальновідомі проблеми з царини теорії поля, фізики конденсованого стану та аналітичної механіки, де зв'язок між суттєвою нелінійністю та високою симетрією є очевидним, хоча не повністю зрозумілим.